Results of Survey on Faculty Members Pursuing Graduate Degrees and Appointment of Graduate Faculty - Council of Graduate Schools in the U.S., Washington, DC.; Council of Graduate Schools in the U.S., Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
A small group of Association of American Universities (AAU) institutions was surveyed by the graduate school at the University of Florida in 1987 as part of a review of its own policies on faculty members pursuing graduate degrees and appointment to the graduate faculty. This was intended to give the graduate council a basis for comparison with other universities. Of the 55 questionnaires mailed to the graduate school deans, 40 were returned (with 20 from state universities and 20 from private universities). The questionnaire asked whether a faculty member holding a tenure-accruing position could pursue a graduate degree in the same institution, and if yes, what restrictions applied. It also asked whether there were university criteria for appointment to the graduate faculty. Results indicate a great difference between state and private universities on the policy of allowing tenure-accruing faculty to pursue graduate degrees in the institution. Restrictions cited include avoiding all possible conflict of interests; approval by the employment unit chairperson and dean, graduate school dean, and vice president for academic affairs; and having a different degree-seeking department from the employment unit. The state and private institutions also differ greatly in terms of the appointment of graduate faculty, with 60% of the state universities having a graduate faculty appointment system and only 30% of the private institutions having one. Specific responses of each university are summarized. (SM)
CGS Communicator, v21 n2 p1-4 Feb-Mar 1988.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrative Policy; College Faculty; Faculty College Relationship; Graduate School Faculty; Graduate Study; Higher Education; National Surveys; Private Colleges; Questionnaires; State Universities; Tenure; Association of American Universities; Collected Works, Serials; Reports, Research